Understanding the Role of Internal Communication in Enhancing Managerial Effectiveness: A Literature-Based Analysis - Novitasari Novitasari (Eduvest - Journal of Universal Studies, 2025)
In the current dynamic business landscape, managerial effectiveness is increasingly recognized as a critical factor in organizational success. This paper explores the role of internal communication in enhancing managerial effectiveness through a literature-based analysis. Drawing on frameworks such as Relationship Management Theory, Dialogic Communication, and the Job Demands-Resources Model, the study highlights how internal communication contributes to trust-building, employee engagement, motivation, and leadership credibility. Findings from previous research show that clear, transparent, and two-way communication improves decision-making, reduces workplace stress, and fosters a positive organizational culture. In contrast, poor communication practices lead to confusion, disengagement, and reduced productivity. The literature also emphasizes the growing need for digital communication skills among managers, especially in hybrid and remote work environments. The paper concludes that internal communication is not merely a support function but a key leadership tool essential for effective management in today’s complex organizations. Organizations that prioritize communication training and cultural alignment are more likely to cultivate effective leaders and long-term success. This study encourages future research on the intersection of communication, leadership, and technology in modern business contexts.